DIVERSITY OF BUTTERFLIES (Lepidoptera: Rhopalocera) IN THE GUNUNG RAYA WILDLIFE RESERVE, SUB DISTRICT WARKUK RANAU, SOUTH SUMATERA - Aprillia, Ina; Yustian, Indra; Setiawan, Arum; Setiawan, Doni (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2018)
This study aims to determine the diversity of butterflies at the Gunung Raya Wildlife Reserve, South Sumatra. The research was conducted in January-February 2018. The research sites were 4 different habitat types, namely primary forest, secondary forest, riparian area, and bush and plantation. Data collection uses direct observation and capture techniques along the transect line (linear transect counting) along 1000 m in each habitat type using insect nets. The results of the study obtained 55 butterfly species belonging to 5 families (there were 13 species of Papilionidae, 30 species of Nymphalidae, 7 species of Pieridae, 1 species of Riodinidae, and 4 species of Lycaenidae). The highest Shanon diversity index is in primary forest habitat (Manduriang) with H'= 3.5; followed by shrubs and plantations (Pasir Bintang) with H'= 3.45, and riparian areas (Talang Lebong) with H' = 3.23; while the lowest is secondary forest (Mesagih) with H'= 2.94. Distribution of species in all locations Â is relative (E> 0.9) and high species richness (R> 4). 2 butterfly species protected by Regulations of the Environtment and Forestry Ministers No 20 of 2018, namely Troides helena and Trogonoptera brookiana has been found in this study.